SAT0565 Reliability of The Quantitative Assessment of Peripheral Blood Perfusion by Laser Speckle Contrast Analysis in A Systemic Sclerosis Cohort. (15th July 2016) - Lambrecht, V.; Cutolo, M.; De Keyser, F.; Decuman, S.; Ruaro, B.; Sulli, A.; Deschepper, E.; Smith, V.; ,
Abstract : Background: In systemic sclerosis (SSc) there is increasing interest to evaluate blood perfusion in a dynamic way, to evaluate evolution of disease and response to therapy. Laser speckle contrast analysis (LASCA) is an emerging technique that measures peripheral blood perfusion (PBP) in real time over a large area and is convenient in use (1, 2). In order to be used as an outcome measure, first reliability of LASCA needs to be attested. Objectives: To investigate the reliability of the quantitative assessment of PBP by LASCA between two raters in a SSc cohort. Methods: Two independent raters evaluated PBP in 40 consecutive patients with SSc (according to the 2013 ACR/EULAR classification criteria) using LASCA. After acclimatization for 20 minutes in a temperature controlled room, PBP was measured at the level of the fingertips, dorsal and volar bilaterally, for 30 sec each. Measurements were performed under standardized environmental, patient and instrumental conditions. PBP values were reported as perfusion units (PU) by creating regions of interest with fixed 1 cm diameter at central area of the fingertips. Mean PU per finger, left and right, dorsal and volar, per rater was calculated. Inter rater reliability was assessed by calculation of intraclass correlation coefficients (ICC). Patients with flexion contractures (n=6) were excluded because they could not meet the standardization requirements. Results: ICC (95% confidence interval) values for PBP measurements varied from 0.82 (0.67 to 0.91) to 0.91 (0.83 to 0.96) for the dorsal fingertips, and from 0.74 (0.55 to 0.86) to 0.86 (0.74 to 0.93) for the volar fingertips (Table 1 ). Conclusions: This is the first study to demonstrate reliability of the quantitative assessment of peripheral blood flow by LASCA in a SSc cohort between two raters, performed under standardized patient, instrumental and environmental conditions. With this study, we took the first step in the validation of LASCA, though further studies are needed to confirm these results. References: Cutolo M, et al. Assessing microvascular changes in systemic sclerosis diagnosis and management. Nat Rev Rheumatol 2010;6:578–87. Ruaro B, et al. Laser speckle contrast analysis: a new method to evaluate peripheral blood perfusion in systemic sclerosis patients. Ann Rheum Dis 2014;73(6):1181–5. Disclosure of Interest: None declared